Impact of poor-quality medicines in the 'developing' world. - Newton, P; Green, MD; Fernández, F (2010)
Since our ancestors began trading several millennia ago, counterfeit and substandard medicines have been a recurring problem, with history punctuated by crises in the supply of anti-microbials, such as fake cinchona bark in the 1600s and fake quinine in the 1800s. Unfortunately this problem persists, in particular afflicting unsuspecting patients in 'developing' countries. Poor-quality drugs are a vital (but neglected) public health problem. They contribute to a 'crevasse' between the enormous effort in therapeutic research and policy decisions and implementation of good-quality medicines.